Evaluasi Program Pendampingan Guru TK Ummi Adniah NWDI Pancor melalui Komunitas Belajar dalam Meningkatkan Kompetensi Pedagogik - Pujianti, Baiq Nur Izwana; Jaelani, Abdul Kadir (Mataram University, 2026)
This study aims to evaluate the effectiveness of a Teacher Mentoring Program through Learning Communities in improving teachers’ pedagogical competence at the secondary school level. Learning communities serve as collaborative platforms designed to encourage teachers to share best practices, engage in discussions, and collectively address instructional challenges. The evaluation method employed was the CIPP model (Context, Input, Process, Product). The evaluation results indicate that, from the context aspect, the program aligns well with teachers’ needs in responding to the implementation of a new curriculum and increasing demands for instructional quality. In terms of input, support from school principals, the availability of learning resources, and facilitator training were found to be adequate. Regarding the process aspect, activities were conducted on a weekly basis; however, not all teachers actively participated. From the product aspect, improvements were observed in teachers’ abilities to design teaching modules, manage classrooms, and implement innovative instructional methods, although the improvement was not evenly distributed across all subject areas. This study recommends strengthening individualized mentoring, optimizing monitoring mechanisms, and enhancing teacher motivation to encourage more active participation.